The Gasoline Climate Trap - Josse Delfgaauw; Otto Swank (Tinbergen Institute, 2023)
Due to taxes and subsidies, gasoline prices vary dramatically across countries. Externalities cannot fully account for this. We develop a simple political-economic model that shows that group interests, resulting from the composition of a country's car fleet, help to explain differences in gasoline taxes even among countries with identical fundamentals. In the model, citizens' car ownership is endogenous, which can yield multiple equilibria. Our model demonstrates the possibility of a society in a climate trap where a low gasoline tax reflects the views of a majority, but another majority would benefit from transitioning to an equilibrium with a higher gasoline tax and fewer emissions.
Keywords: D62; D72; H23; Q58; 330; median voter; gasoline taxes; multiple equilibria.